Peran Sumber Ilmu dalam Pembentukan Kurikulum Pendidikan Islam Berbasis SDG 4 Perspektif Hadis Tarbawi - Yoga Adhitya Fredy Firmansyah; Nur Mila Zakkiyah; Nasywa Annisa Syabana; Ahmad Yusam Thobroni (LPPM Politeknik Piksi Ganesha, 2026)
This study examines the classification of sources of knowledge in Islamic education and its impact on the learning process in line with SDG 4. The methodology employed is narrative in nature, based on a review of the literature on exegesis and educational hadith. The research findings reveal that sources of knowledge include the Word of God, reason, empirical practice, and integrated social reality. These references are categorised into naqli and aqli, which mutually reinforce one another. Within the syllabus, both form the foundation for the formulation of objectives and teaching strategies. Educational hadiths reinforce the principles of exemplary conduct and character. This integration helps to realise excellent, open, and sustainable education, producing students who are intelligent, ethical, and socially committed within an increasingly advanced contemporary community